Enhancing circular economy through industrial symbiosis: An agent-based simulation analysis of supply chain dynamics - Rebecca Fussone; Caterina Sammatrice; Salvatore Cannella; Roberto Dominguez (Sustainable Operations and Computers)
Industrial Symbiosis is recognized in the international context as a useful approach to move toward a Circular Economy. Here, the use of resources in industrial systems is improved, since waste and by-products generated by a firm are upcycled and used as input by other firms, reducing raw material extraction and waste sent to landfills. This work presents an analysis of the dynamic performance when an industrial symbiosis is implemented between two supply chains, where one represents the supplier of the other. Specifically, using the agent-based modeling simulation approach, the behavior and dynamics of the symbiotic supply chain are evaluated in different scenarios by adopting key performance indicators, such as the efficiency of symbiotic exchange, the environmental index, and the bullwhip effect. Based on our analysis, we provide useful managerial suggestions to create supportive and collaborative supply chains to support the Circular Economy.